Altered Serum Immunological and Biochemical Parameters and Microbiota Composition in Patients With AN During Realimentation - Roubalova, Radka; Prochazkova, Petra; Dvorak, Jiri; Hill, Martin; Papezova, Hana; Kreisinger, Jakub; Bulant, Josef; Lambertova, Alena; Holanova, Petra; Bilej, Martin; Tlaskalova-Hogenova, Helena (Frontiers in Nutrition, 2021)
Anorexia nervosa (AN) is a life-threatening psychiatric disorder with not well-described pathogenesis. Besides the genetic and sociological factors, autoimmunity is also considered to take part in AN pathogenesis. We evaluated general serological factors showing the physiological state of fifty-nine patients with AN at hospital admission and their discharge. We detected the altered levels of some general biochemical and immunological parameters. We also detected decreased levels of appetite-regulating alpha-melanocyte stimulating hormone (-MSH) in patients at hospital admission. Moreover, elevated anti--MSH IgM levels and decreased anti--MSH IgA levels were observed in patients with AN. Therefore, we analyzed the gut microbiota composition with special focus on -MSH antigen-mimetic containing microbes from the Enterobacteriaceae family. We correlated gut bacterial composition with anti--MSH Ig levels and detected decreasing IgG levels with increasing alpha diversity. The upregulation of pro-inflammatory cytokines IL-6, IL-17, and TNF- were detected in patients with AN both prior and after hospitalization. We also evaluated the treatment outcome and improvement was observed in the majority of patients with AN. We provide new data about various serum biochemical parameters and their changes during the patients’ hospitalization, with emphasis on the immune system, and its possible participation in AN pathogenesis.